2018
DOI: 10.1186/s13075-018-1544-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for oral methotrexate failure in patients with inflammatory polyarthritis: results from a UK prospective cohort study

Abstract: BackgroundOral methotrexate (MTX) is the first-line therapy for patients with rheumatoid arthritis (RA). However, approximately one quarter of patients discontinue MTX within 12 months. MTX failure, defined as MTX cessation or the addition of another anti-rheumatic drug, is usually due adverse event(s) and/or inefficacy. The aims of this study were to evaluate the rate and predictors of oral MTX failure.MethodsSubjects were recruited from the Norfolk Arthritis Register (NOAR), a primary care-based inception co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 23 publications
4
21
0
1
Order By: Relevance
“…People with longer history of illness and MTX treatment significantly more often give up further therapy, which is in concordance with previous results reported in the literature 6 . In Bluett et al observation in cohort recruited from Norfolk Arthritis Register of early inflammatory polyarthritis, 2 years of therapy continuation was observed in 82% of patients and 5 years in 72% 16 . In older studies percentage of patients continuing treatment after 2 and 5 years was much lower, respectively, 53% 17 and 45%‐57.1% 18,19 …”
Section: Discussionsupporting
confidence: 90%
“…People with longer history of illness and MTX treatment significantly more often give up further therapy, which is in concordance with previous results reported in the literature 6 . In Bluett et al observation in cohort recruited from Norfolk Arthritis Register of early inflammatory polyarthritis, 2 years of therapy continuation was observed in 82% of patients and 5 years in 72% 16 . In older studies percentage of patients continuing treatment after 2 and 5 years was much lower, respectively, 53% 17 and 45%‐57.1% 18,19 …”
Section: Discussionsupporting
confidence: 90%
“…In the Utrecht RA cohort established in 1990, 36% of the patients achieved at least one period of remission; among other predictors, RF negativity was associated with 1.63 hazards of achieving remission (77). IgM RF positive patients were less likely to achieve remission also in other cohorts (78, 79), and a recent study on early RA patients commencing methotrexate (MTX) as their first disease modifying anti-rheumatic drug (DMARD) within 3 months of their baseline visit confirmed that RF was associated with earlier MTX failure due to inefficacy (80). In contrast, the predictive value of ACPA for achieving point remission is not that obvious.…”
Section: Autoantibodies and Disease Remissionmentioning
confidence: 99%
“…Moreover, the presence of IgM RF in patient sera renders clinical remission less achievable. In fact, a recent study reported that RF is associated with early methotrexate (MTX) failure due to inefficacy in patients with early RA [ 136 ].…”
Section: Monitoring Ra Disease Activity and Progression With Rf Amentioning
confidence: 99%